DOI: 10.11606/t.11.2006.tde-23082006-152138
|View full text |Cite
|
Sign up to set email alerts
|

Variação sazonal da fotossíntese e relações hídricas de laranjeira 'Valência'

Abstract: A Deus, aos meus antepassados e aos meus pais Cláudio e Marilena pela vida.Aos meus familiares, minhas irmãs Mônica, Simone, Renata, tia Cláudia e avós Darci e Dinarcy por estarem sempre presentes em minhas conquistas, mesmo que distantes fisicamente.À minha amada esposa Ilana por compartilhar a sua vida comigo e me proporcionar toda a tranqüilidade necessária para o desenvolvimento desse estudo.Ao amigo Eduardo C. Machado (IAC) pelo constante incentivo e orientação durante minha formação acadêmica, exemplo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
4

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(45 citation statements)
references
References 163 publications
0
41
0
4
Order By: Relevance
“…Based on these data, the water use efficiency [(µmol m -2 s -1 ) (mol H2O m -2 s -1 ) -1 ] and the instantaneous efficiency of carboxylation Фc were quantified (Neves et al, 2002;Konrad et al, 2005;Ribeiro, 2006). Source: Analyses carried out in the soil laboratory of the Science and Technology Center Agrifood, UFCG.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these data, the water use efficiency [(µmol m -2 s -1 ) (mol H2O m -2 s -1 ) -1 ] and the instantaneous efficiency of carboxylation Фc were quantified (Neves et al, 2002;Konrad et al, 2005;Ribeiro, 2006). Source: Analyses carried out in the soil laboratory of the Science and Technology Center Agrifood, UFCG.…”
Section: Methodsmentioning
confidence: 99%
“…Such effects may be caused by the low values of soil temperatures (Magalhães Filho et al, 2009), soil water availability (Ribeiro & Machado, 2007) and also by high vapor pressure deficits (Habermann et al, 2003) observed during the dry season in subtropical areas (Ribeiro & Machado, 2007;Habermann & Rodrigues, 2009). Significant reductions in the water use efficiency have been reported for irrigated field-grown citrus plants during the dry season (Ribeiro, 2006), which confirm that other factors, other than soil water availability, may affect the photosynthesis of citrus plants (Ribeiro & Machado, 2007). These effects may have significant consequences for fruit production, when considering different regions, with different micro-climates and different disease pressures and their physiological damages for plants (Habermann & Rodrigues, 2009).…”
Section: Root System Water Absorption/use Strategies In Citrus and Cmentioning
confidence: 66%
“…À medida que a planta perde água para a atmosfera via transpiração, vai ocorrendo aumento na tensão da coluna de água no interior dos vasos de xilema. Essa variação diurna de Ψ f ocorre mesmo em plantas com boa disponibilidade hídrica no solo e, em média, esses valores de Ψ f , em laranjeira 'Valência', variam entre -0,4 e -2,4 MPa ao longo do dia (Syvertsen & Albrigo, 1980;Ribeiro, 2006).…”
Section: Resultsunclassified
“…Em trabalho com laranjeira 'Valência', Ribeiro (2006) também obteve menores (p<0,05) valores de Ψ f14 na face oeste, tanto em plantas irrigadas, quanto em condições de sequeiro. A incidência solar direta, aliada a maior temperatura e a menor umidade relativa do ar, no período da tarde, são fatores que levam ao aumento da diferença de pressão de vapor entre a folha e o ar na face oeste, redundando em maior transpiração e a consequente redução de Ψ f14 .…”
Section: Resultsunclassified
See 1 more Smart Citation